2004
DOI: 10.1029/2004gl019558
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale of high‐speed flows in the plasma sheet observed by Cluster

Abstract: [1] Spatial gradients of high-speed flows in the midtail plasma sheet are determined using multipoint observations from the Cluster spacecraft along the ''dawn-dusk'' direction (perpendicular to the main flow and in the plane of the tail current sheet) and along the north-south direction. If we take the average or median of the spatial gradients and assume that the flow channel has a linear gradient, these values suggest that the full width of the flow channel is 2-3 R E in the ''dawn-dusk'' direction and 1.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
332
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 326 publications
(384 citation statements)
references
References 23 publications
(32 reference statements)
51
332
0
1
Order By: Relevance
“…[60] Comparing the ECR and BBF scale sizes, observational investigations have confirmed that BBFs are narrow and elongated structures, whose cross-tail scale size is of the order of 1 or a few R E [e.g., Sergeev et al, 1996a;Angelopoulos et al, 1997;Nakamura et al, 2004Nakamura et al, , 2005aWalsh et al, 2009]. Walsh et al [2009] estimated that the BBF size along the direction of the plasma flow is approximately ∼4R E .…”
Section: Ecr Scale Sizementioning
confidence: 99%
“…[60] Comparing the ECR and BBF scale sizes, observational investigations have confirmed that BBFs are narrow and elongated structures, whose cross-tail scale size is of the order of 1 or a few R E [e.g., Sergeev et al, 1996a;Angelopoulos et al, 1997;Nakamura et al, 2004Nakamura et al, , 2005aWalsh et al, 2009]. Walsh et al [2009] estimated that the BBF size along the direction of the plasma flow is approximately ∼4R E .…”
Section: Ecr Scale Sizementioning
confidence: 99%
“…Generally, this is observed during substorms or strong reconnection, as has been reported in the literature (e.g., Nosé et al, 2000a, b;Ono et al, 2009;Keika et al, 2013;Luo et al, 2014). Since the energization process has been observed to happen during substorms and localized dipolarization of the magnetic field, the acceleration process can be considered "local".…”
Section: Energy Gainmentioning
confidence: 86%
“…In the presence of substorms and local dipolarization of magnetic field, the most energized species is found to be oxygen, reaching energies larger than 200 keV (Nosé et al, 2000a, b;Ono et al, 2009;Luo et al, 2014). During those periods the magnetic fluctuations are generated by reconnection jets and produce a spatially localized acceleration of ions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations